WOMEN WRITERS IN THE MIDDLE EAST AND IN THE WEST - Diane d’Almeida (European Scientific Journal, ESJ, 2014)
Trips to Morocco and Jordan, and later to Syria, have allowed me to pursue my interest of literature coming from the Arab world. I received a grant from the US government to visit and research libraries in Morocco and Jordan. As a librarian I studied practices that were used in these different countries in their own libraries, and contributed best practices in the United States to local staff. My expertise came from experience at state of the art university libraries and study at Simmons College. During the second Fulbright I filmed women writers and created two websites (http://www.bu.edu/library/guide/caww/ ) and (http://www.womenwritersoftheworld.com/). In my paper I discuss the positive aspects of reading the literature of another culture. I also discuss the women who I video-taped – both Middle Eastern women and Westerners. Those from the Middle East come from: Iraq, Palestine, Jordan, and Syria. Women from the West who I videoed are from: Scotland, India/Germany, Boston and other local areas. All of them are dedicated and are passionate about their professions as writers despite the many obstacles they have encountered. Some have other occupations. Some have families. There are similarities between then – both between the West and the East, and among themselves – that are curious. Understanding other cultures through the writings of these women, and the reading of their works, is instrumental in banishing stereotypes that the media send our way every day. Misconstrued ideas of other cultures can drive public attitudes and policies in unexpected and destructive directions.